Household debt: impact of Mortgage financing towards banking institutions in Malaysia / Juriah Jamalludin - Jamalludin, Juriah (Faculty of Business and Management, 2011)
Analyst and statistical data reported a rapid growth in household debt since the 1997 Asian financial crisis. This upward trend scenario is worrying if its left unchecked will develop a household credit bubble in the banking industry. On the other hand, there is lack of study exploring the relationship between loan growth and economic indicators. Therefore, this study tries to extend the body of knowledge by analyzing the status of Malaysian household debt in general and Mortgage financing in details by using four selected economic indicators namely, Malaysia House Price Indictor (MHPI), Base Lending Rates (BLR), Gross National Income Per Capita (GNI/C) and Non-Performing Loan (NPL). The linear regression model on single and multiple relationship was applied towards the quarterly time series and cross sectional data for period of 11 years start from 1st Quarter of 2000 to 4th Quarter of 2010. The results on single relationship show that there is a relationship between independent and dependent variable while, the result on multiple relationship shows that dependent variable is affected by only 3 independent variable namely, MHPI, BLR and GNI/C. Eventually, the result from this study will create awareness to the government, regulators, investors, banking industry and even the household itself to look closely into this issue.